Genome-wide identification, characterization and expression of C2H2 zinc finger gene family in Opisthopappus species under salt stress - Xiaojuan Zhou; Ting Gao; Yimeng Zhang; Mian Han; Yuexin Shen; Yu Su; Xiaolong Feng; Qi Wu; Genlou Sun; Yiling Wang (BMC Genomics, 2024)
Abstract Background The C2H2 zinc finger protein family plays important roles in plants. However, precisely how C2H2s function in Opisthopappus (Opisthopappus taihangensis and Opisthopappus longilobus) remains unclear. Results In this study, a total of 69 OpC2H2 zinc finger protein genes were identified and clustered into five Groups. Seven tandem and ten fragment repeats were found in OpC2H2s, which underwent robust purifying selection. Of the identified motifs, motif 1 was present in all OpC2H2s and conserved at important binding sites. Most OpC2H2s possessed few introns and exons that could rapidly activate and react when faced with stress. The OpC2H2 promoter sequences mainly contained diverse regulatory elements, such as ARE, ABRE, and LTR. Under salt stress, two up-regulated OpC2H2s (OpC2H2-1 and OpC2H2-14) genes and one down-regulated OpC2H2 gene (OpC2H2-7) might serve as key transcription factors through the ABA and JA signaling pathways to regulate the growth and development of Opisthopappus species. Conclusion The above results not only help to understand the function of C2H2 gene family but also drive progress in genetic improvement for the salt tolerance of Opisthopappus species.